The Nexus Between Green Energy, Energy Economics, and Sustainable Development: A Bibliometric Review - Hai, Ho Tran Quoc; Tuan, Vuong Khanh (International Journal of Energy Economics and Policy, 2025)
Despite sustainability research being one of the fastest-growing themes, most existing analyses either focus on specific themes or regional contexts, failing to provide a view of the broader global landscape or the linkages among economic, technological, and policy-oriented perspectives. This study conducts a deep bibliometric analysis of the intellectual structure, trends, and worldwide dynamics of research related to sustainable development, energy economics, and environmental management. The analysis aims to highlight how the discourse has evolved over time and identify the institutions and countries that drive the discourse, as well as the journals that represent the most common knowledge outlets. A total of 309 articles published from 1998 to 2025 were identified on the Web of Science database and selected for analysis. A sharp increase in indexed publications is observed after 2019, led by China, the United States, and India. Keyword mapping and bibliographic coupling show that terms such as “sustainable development,” “energy,” “climate change,” and “innovation” are at the core of increasingly interdisciplinary and empirical research. In practical terms, the study informs policymakers, funding institutions, and academic institutions on how to better target collaborations, set research priorities that meet global sustainability agendas, and translate knowledge into policy and innovation outcomes. In theoretical terms, it articulates how sustainability-related research has moved from conceptual debates to evidence-based and policy-relevant applications of data-driven analyses, enriching the emerging academic discourse on sustainable transformation and the global energy transition.